Effective Treatment Strategies for Adults with Type 2 Diabetes - Czerska, Magdalena Agata; Wójcik, Zofia Martyna; Kamińska-Omasta, Katarzyna; Omasta, Bartosz; Krupa, Olga; Pietrukaniec , Paulina Dorota; Romańczuk, Kuba Borys; Furtak , Kinga; Stolarczyk, Szymon Przemysław; Rybak, Daria (Quality in Sport, 2025)
Introduction Type 2 diabetes is a chronic metabolic disorder marked by insulin resistance and insufficient insulin production. It affects millions globally, with 537 million adults diagnosed in 2021, a prevalence that has doubled from 7% in 1990 to 14% in 2022. This rise imposes a significant burden on individuals, healthcare systems, and economies. Aim of the Study This study aims to provide an overview of therapeutic management for type 2 diabetes, focusing on pharmacological treatments and their integration with lifestyle changes, such as diet and exercise, to improve outcomes and reduce complications. Materials and Methods The study reviews literature and clinical guidelines on managing type 2 diabetes, emphasizing pharmacological treatments like insulin, oral hypoglycemic agents, and newer therapies. It also examines the role of diet and physical activity in controlling blood glucose and preventing complications. Data sources include peer-reviewed articles and health organization publications from the past ten years, targeting adults aged 18 and older. Summary Type 2 diabetes remains a global health challenge with rising prevalence. Effective management requires a combined approach of pharmacological therapies and lifestyle modifications, underscoring the importance of early intervention to reduce complications and improve outcomes.